(untitled) - Suzuki, David T. (Boston, 1990)
From Naked Ape to Super Species takes an unflinching look at where we are at this unprecedented moment in history. Suzuki and Dressel reveal that a clear and present environmental danger is staring us in the face, a danger that is screened out by perceptual filters formed by our current values and beliefs. And should the truth get through to us, we experience a paralysis in the face of adversity that is fueled by a sense of impotence and by the psychological and institutional barriers that stymie us.But there is good news. Experts maintain we still has time to avoid this breakdown if we slow down and turn onto alternative roads that will lead to a life still rich in opportunity, choice, and quality. But to begin applying brakes and turning aside, we must see with clarity the we're on now, how we got here, and what the other possibilities are.
Keywords: Science,Khoa học; Social aspects,Khía cạnh xã hội